Therapeutic application of quercetin in aging-related diseases: SIRT1 as a potential mechanism - Cui, Zhifu; Zhao, Xingtao; Amevor, Felix Kwame; Du, Xiaxia; Wang, Yan; Li, Diyan; Shu, Gang; Tian, Yaofu; Zhao, Xiaoling (Frontiers in Immunology, 2022)
Quercetin, a naturally non-toxic flavonoid within the safe dose range with antioxidant, anti-apoptotic and anti-inflammatory properties, plays an important role in the treatment of aging-related diseases. Sirtuin 1 (SIRT1), a member of NAD+-dependent deacetylase enzyme family, is extensively explored as a potential therapeutic target for attenuating aging-induced disorders. SIRT1 possess beneficial effects against aging-related diseases such as Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), Depression, Osteoporosis, Myocardial ischemia (M/I) and reperfusion (MI/R), Atherosclerosis (AS), and Diabetes. Previous studies have reported that aging increases tissue susceptibility, whereas, SIRT1 regulates cellular senescence and multiple aging-related cellular processes, including SIRT1/Keap1/Nrf2/HO-1 and SIRTI/PI3K/Akt/GSK-3β mediated oxidative stress, SIRT1/NF-κB and SIRT1/NLRP3 regulated inflammatory response, SIRT1/PGC1α/eIF2α/ATF4/CHOP and SIRT1/PKD1/CREB controlled phosphorylation, SIRT1-PINK1-Parkin mediated mitochondrial damage, SIRT1/FoxO mediated autophagy, and SIRT1/FoxG1/CREB/BDNF/Trkβ-catenin mediated neuroprotective effects. In this review, we summarized the role of SIRT1 in the improvement of the attenuation effect of quercetin on aging-related diseases and the relationship between relevant signaling pathways regulated by SIRT1. Moreover, the functional regulation of quercetin in aging-related markers such as oxidative stress, inflammatory response, mitochondrial function, autophagy and apoptosis through SIRT1 was discussed. Finally, the prospects of an extracellular vesicles (EVs) as quercetin loading and delivery, and SIRT1-mediated EVs as signal carriers for treating aging-related diseases, as well as discussed the ferroptosis alleviation effects of quercetin to protect against aging-related disease via activating SIRT1. Generally, SIRT1 may serve as a promising therapeutic target in the treatment of aging-related diseases via inhibiting oxidative stress, reducing inflammatory responses, and restoring mitochondrial dysfunction.